Financing SMEs in Mongolia by bank - Munkhbayasgalan Temuulen (2021)
Small and medium-sized enterprises (SMEs) make significant contribute to increasing the competitiveness of economy by implementing best practices in the production and management spheres. The development of SMEs contributes to an increase in employment and self-employment of the population, stimulates greater responsibility for the growth of their own welfare. Development of any business requires diversification of financial sources. The main source of funding for SMEs in Mongolia is commercial banks. But lack of credit history and collateral are a barrier to attracting bank financing. In the thesis, theoretical aspects were developed also the essence and basic concept of small and medium businesses were disclosed. The tools of financial support for small and medium-sized businesses and their evaluation were revealed. The well-functioning mechanism of work between banks, large financial opportunities and small arrears will help to implement programs of financial support for SMEs. Consequently, the creation of financial support for small and medium-sized businesses will contribute to the development of small and medium-sized businesses and increase their income.